Internal exile in Fascist Italy : history and representations of confino - Garofalo, Piero; Leake, Elizabeth; Renga, Dana, 1971- (Manchester University Press, 2019)
This book is an accessible history of internal exile's origins and practices under Fascism and of its representation in film, literature and memoir.
Keywords: Bibel -- Philemonbrief; Fascism -- Italy -- 1945-; Political prisoners -- Italy -- History -- 20th century.; Detention of persons -- Italy -- History -- 20th century.; Fascisme -- Italie -- 1945-; Prisonniers politiques -- Italie -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; POLITICAL SCIENCE -- General.; Detention of persons; Fascism; Political prisoners; Italy; Innere Emigration; Faschismus; Literatur; Italien; Since 1900; History